Epiretinal stimulation with local returns enhances selectivity at cellular resolution. (6th February 2019) - Fan, Victoria H; Grosberg, Lauren E; Madugula, Sasidhar S; Hottowy, Pawel; Dabrowski, Wladyslaw; Sher, Alexander; Litke, Alan M; Chichilnisky, EJ
Abstract: Objective . Epiretinal prostheses are designed to restore vision in people blinded by photoreceptor degenerative diseases, by directly activating retinal ganglion cells (RGCs) using an electrode array implanted on the retina. In present-day clinical devices, current spread from the stimulating electrode to a distant return electrode often results in the activation of many cells, potentially limiting the quality of artificial vision. In the laboratory, epiretinal activation of RGCs with cellular resolution has been demonstrated with small electrodes, but distant returns may still cause undesirable current spread. Here, the ability of local return stimulation to improve the selective activation of RGCs at cellular resolution was evaluated. Approach . A custom multi-electrode array (512 electrodes, 10 μ m diameter, 60 μ m pitch) was used to simultaneously stimulate and record from RGCs in isolated primate retina. Stimulation near the RGC soma with a single electrode and a distant return was compared to stimulation in which the return was provided by six neighboring electrodes. Main results . Local return stimulation enhanced the capability to activate cells near the central electrode (<30 μ m) while avoiding cells farther away (>30 μ m). This resulted in an improved ability to selectively activate ON and OFF cells, including cells encoding immediately adjacent regions in the visual field. Significance . These results suggest that a device that restricts the electric field through local returns could optimize activation of neurons at cellular resolution, improving the quality of artificial vision.